Exchange Rate Regimes in Selected Advanced Transition Economies : Coping with Transition, Capital Inflows, and EU Accession. (IMF Policy Discussion Papers; Policy Discussion Paper, 2000)
Since beginning economic transition, the Czech Republic, Estonia, Hungary, Poland, and Slovenia have-with much success-employed diverse exchange rate regimes. As these countries approach EU accession, they will need to avoid the perils of too much or too little exchange rate variability when capital flows are likely to be large and volatile; narrow band arrangements in particular could be problematic. The exception is Estonia, where there are good arguments for retaining the currency board arrangement. Countries wishing to join the euro area at an early stage should not leave the removal of remaining capital controls to the last minute.